Ketogenic Diet‐Associated Worsening of Osteoarthritis Histologic Secerity, Increased Pain Sensitivity and Gut Microbiome Dysbiosis in Mice - Gabby Dyson; Montana Barrett; Leoni Schlupp; Emmaline Prinz; Nicholas Hannebut; Aleksander Szymczak; Cindy Miranda Brawner; Matlock A. Jeffries (ACR Open Rheumatology)
Objectives Dietary interventions are a potentially powerful treatment option for knee osteoarthritis (OA). The objective of this study was to evaluate a well‐formulated ketogenic diet (KD) in the context of knee OA histology and pain using the destabilization of the medial meniscus (DMM) mouse model and correlate with gut microbiome and systemic cytokine levels. Methods Adult male mice underwent unilateral DMM or sham surgery and were then fed eight weeks of KD or chow. At baseline and every two weeks, mechanical allodynia of the operated and contralateral knees was assessed via analgesiometry. Knee joints were collected for histology, gut microbiome analysis was performed on cecal material via 16S sequencing, and serum cytokines were analyzed via Bio‐Plex assay. Results KD mice had worse histopathologic OA after DMM (mean ± SEM Osteoarthritis Research Society International score: KD‐DMM: 4.0 ± 0.5 vs chow‐DMM: 2.7 ± 0.08; P = 0.02). KD mice had increased mechanical allodynia postsurgery (P = 0.005 in mixed‐effects model). The gut microbiome changed substantially with KD: 59 clades were altered by KD in DMM and 39 by KD in sham (36 were shared, 25 overlapped with previous murine OA studies). Several clades were correlated on an individual‐mouse level with both histology and allodynia (eg, Lactobacillus histology P = 0.004, allodynia P = 1 × 10−4). Serum analysis showed four cytokines increased with KD (interleukin [IL]‐1β, IL‐2, IL‐3, and IL‐13). Conclusion KD started immediately after OA induction via DMM is associated with worsened histologic outcomes. KD also worsens mechanical allodynia after either DMM or sham surgery. KD induces significant gut microbiome dysbiosis in clades previously associated with murine OA.